Peningkatan Omset Toko Berbasis Online Shop dengan Lifestyle Komsumtif di Kota Langsa - Hamidah Hanim; Zakia Tutdin; Elisa Putri Syah (the Faculty of Education and Teacher Training of the Institut Agama Islam Negeri (IAIN) Langsa, 2022)
The online store business provides many opportunities in growing opportunities and important implications for the transformation of business transactions and becomes an important part of increasing company productivity. Designing an online store business can help support regional economic growth without a large investment. The rise of online shop shops because online shop shops offer products at affordable prices. This research method uses qualitative research methods. The qualitative description method is a research method in which the collected data appears in the form of words, pictures, not numbers. There are several research findings, namely first, there is an increase in the consumptive lifestyle of the people of Kota Langsa based on online shops. Second, from the three informants, it is known that two of them experienced an increase in sales turnover, which was marked by an increase in consumers coming to shop, as well as an increase in the number of resellers. Third, there was a decrease in sales turnover at the Ayyang Galeri store due to the emergence of more and more online shops